Cellulose nanocrystal as well as preparation method and application thereof

By carboxylation and sulfonic acid-based bigroup modification of cellulose, cellulose nanocrystals with bigroups were prepared, which solved the shortcomings of existing nanomaterials in terms of adhesion and ionic conductivity, and achieved the effect of significantly improving the adhesion ability and ionic conductivity in battery applications.

CN119775443APending Publication Date: 2025-04-08GUILIN SAILUNA TECHNOLOGY CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411867226.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-18
Publication Date
2025-04-08

AI Technical Summary

Technical Problem

In use, existing cellulose nanomaterials have problems such as good adhesion but poor ionic conductivity, or poor adhesion but good ionic conductivity, making it difficult to meet the needs of better adhesion and ionic conductivity at the same time.

Method used

By carboxylation and sulfonating bigroup modification of cellulose, cellulose nanocrystals with bigroups are prepared, and the bigroup content is regulated by controlling process conditions such as the amount, time, temperature of raw materials for alkalization and etherification, as well as the acid concentration, temperature and time of acid hydrolysis, thereby improving the bonding ability and ionic conductivity of nanomaterials.

Benefits of technology

When cellulose nanocrystals are used in the silicon carbon anode and separator of the battery, it significantly improves the bonding capacity and ionic conductivity, and is suitable for industrial production.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119775443A_ABST
    Figure CN119775443A_ABST
Patent Text Reader

Abstract

The invention discloses a cellulose nanocrystal as well as a preparation method and application thereof, and belongs to the technical field of cellulose nanomaterial preparation. The preparation method of the cellulose nanocrystal comprises the following steps: performing carboxylation modification on cellulose, and then performing sulfonation treatment to obtain carboxylated and sulfated double-group modified cellulose; and performing stripping treatment on the carboxylated and sulfated double-group modified cellulose to obtain the cellulose nanocrystal. The preparation process of the cellulose nanocrystal is high in feasibility, the obtained cellulose nanocrystal has double groups (carboxylation and sulfonylation double groups), the nanoscale, the length-diameter ratio and the content of the double groups are controllable, and the bonding capacity and the ionic conductivity can be remarkably improved when the cellulose nanocrystal is applied to a silicon-carbon negative electrode and a diaphragm of a battery.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of cellulose nanomaterial preparation, and in particular to cellulose nanocrystal and a preparation method and application thereof. Background Art

[0002] Cellulose is one of the most abundant renewable resources in nature today, and is widely found in plants, animals, algae and some bacterial organisms. Nanocellulose refers to cellulose materials with at least one dimension in the nanometer range. It has attracted widespread attention due to its excellent mechanical properties, nanometer size, low density, low thermal expansion coefficient, renewability, biodegradability, non-toxicity and biocompatibility. As a new generation of environmentally friendly nanomaterials, it has great application potential in high-performance composite materials, special paper, food packaging, pharmaceutical preparations, medical engineering, lithium / sodium ion batteries and supercapacitors, cosmetics and other fields.

[0003] At present, there are many reports on the preparation methods of carboxylated nanocellulose and sulfonated nanocellulose, and there are also many applications in related fields. However, carboxylated nanocellulose has better adhesion and poor ion conductivity in applications; sulfonated nanocellulose has better ion conductivity but unsatisfactory adhesion, so it is necessary to study nanocellulose with both good adhesion and ion conductivity. However, there are almost no reports on the preparation methods of cellulose nanocrystals with both carboxyl and sulfonic acid groups on the surface. Summary of the invention

[0004] The purpose of the present invention is to provide a cellulose nanocrystal and a preparation method and application thereof to solve the problems existing in the above-mentioned prior art. The preparation process of the cellulose nanocrystal of the present invention is highly feasible, and the obtained cellulose nanocrystal has a double group (carboxylation and sulfonation double group), and through the alkalization and etherification process conditions and the acid hydrolysis process conditions, the double group content is controllable (the carboxyl content is controlled by controlling the amount of raw materials used, time, and temperature in the alkalization and etherification; the sulfonic acid content is controlled by the acid concentration, temperature, and hydrolysis time of sulfuric acid hydrolysis), and the application in the silicon-carbon negative electrode and diaphragm of the battery can significantly improve the bonding ability and ionic conductivity.

[0005] To achieve the above object, the present invention provides the following solutions:

[0006] One of the technical solutions of the present invention: a method for preparing cellulose nanocrystals, comprising the following steps:

[0007] Carboxylation is performed on cellulose and then sulfonation is performed to obtain cellulose modified with carboxylation and sulfonation groups;

[0008] The carboxylation and sulfonation double-group modified cellulose is subjected to a stripping treatment to obtain the cellulose nanocrystals (carboxylation and sulfonation double-group cellulose nanocrystals).

[0009] Compared with carboxylated nanocellulose and sulfonated nanocellulose, the carboxylated and sulfonated double-group cellulose nanocrystals of the present invention have both sulfonate and carboxylate groups, and therefore have the characteristics of both carboxylated nanocellulose and sulfonated nanocellulose, giving the material new and unique properties, especially in the application field of lithium battery materials, especially silicon-carbon negative electrode materials and diaphragm materials, improving the ionic conductivity while improving the bonding ability.

[0010] Furthermore, the cellulose includes one or more of refined cotton, bleached bagasse or bleached wood pulp.

[0011] Furthermore, the method for carboxylating cellulose comprises the following steps: alkalizing the cellulose and then adding an organic acid to perform a carboxylation reaction to obtain carboxylated cellulose.

[0012] Furthermore, the alkaline reagent used in the alkalization treatment includes potassium hydroxide or sodium hydroxide;

[0013] The temperature of the alkalization treatment is 30-35° C. and the time is 40 minutes.

[0014] Furthermore, the alkaline reagent needs to be prepared into a mixed solution for alkalization treatment; the solvent in the mixed solution includes water and an organic solvent in a volume ratio of 1:(10-15); the mass ratio of the alkaline reagent to water in the mixed solution is 1:10; the organic solvent includes isopropanol and / or anhydrous ethanol.

[0015] Furthermore, when the organic solvent is isopropanol and anhydrous ethanol, the volume ratio of the isopropanol to the anhydrous ethanol is (1-3):1.

[0016] Furthermore, the mass ratio of the cellulose to the alkaline reagent is (1-3):1;

[0017] The molar ratio of the glucose unit in the cellulose to the organic acid is (1-5):1;

[0018] The temperature of the carboxylation reaction is 70° C. and the time is 2 to 4 hours.

[0019] Furthermore, the molar ratio of the glucose unit in the cellulose to the organic acid is (1.5-4):1; the temperature of the carboxylation reaction is 70° C. and the time is 3 hours.

[0020] Furthermore, the organic acid includes one or more of chloroacetic acid, methyl chloroacetate, ethyl chloroacetate and isopropyl chloroacetate.

[0021] Furthermore, the sulfonation treatment method comprises the following steps: mixing the carboxylated cellulose and a sulfuric acid solution to react, thereby obtaining the carboxylated and sulfonated double-group modified cellulose.

[0022] Furthermore, the concentration of the sulfuric acid solution is 45-65 wt.%; the usage ratio of the carboxylated cellulose and the sulfuric acid solution is 1 g: (10-40) mL;

[0023] The reaction temperature is 25-65°C and the reaction time is 2-48 hours.

[0024] Furthermore, the stripping treatment method comprises the following steps: adding the carboxylation and sulfonation double-group modified cellulose into water, adjusting the pH to 6-8, stirring and soaking, and then stripping to obtain the cellulose nanocrystals.

[0025] Furthermore, the peeling method includes high-speed shearing, high-pressure homogenization, ultrasound, ball milling or grinding.

[0026] The second technical solution of the present invention: a cellulose nanocrystal prepared by the above preparation method.

[0027] The third technical solution of the present invention: an application of the above-mentioned cellulose nanocrystals in the preparation of battery negative electrode materials or diaphragms.

[0028] The present invention discloses the following technical effects:

[0029] (1) The preparation process of the cellulose nanocrystals of the present invention is highly feasible (the sulfonation reaction of etherified fibers can be achieved at room temperature, and the energy consumption cost is greatly reduced). The obtained cellulose nanocrystals have double groups (carboxylation and sulfonation double groups), and the nanoscale, aspect ratio, and double group content are controllable. When used in silicon-carbon negative electrodes and separators of batteries, the bonding ability and ionic conductivity can be significantly improved.

[0030] (2) The present invention expands the preparation technology of cellulose nanocrystals and is suitable for promoting the industrial production technology of nanocellulose products containing both carboxyl and sulfonic acid groups.

[0031] (3) The cellulose nanocrystals prepared by the present invention have a crystallinity of more than 74%, and can be used as negative electrode binders to replace carboxymethyl cellulose, thereby improving the binding force and ionic conductivity. BRIEF DESCRIPTION OF THE DRAWINGS

[0032] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0033] Figure 1 This is an appearance diagram of carboxylated and sulfonated bi-group cellulose nanocrystals prepared in Example 1 of the present invention;

[0034] Figure 2 This is a scanning electron microscope image of the carboxylated and sulfonated bi-group cellulose nanocrystals prepared in Example 1 of the present invention;

[0035] Figure 3 This is a transmission electron microscopy image of carboxylated and sulfonated bi-group cellulose nanocrystals prepared in Example 1 of the present invention;

[0036] Figure 4 This is a transmission electron microscopy image of the carboxylated and sulfonated bi-group cellulose nanocrystals prepared in Example 2 of the present invention. DETAILED DESCRIPTION

[0037] Various exemplary embodiments of the present invention will now be described in detail. This detailed description should not be considered as limiting the present invention, but should be understood as a more detailed description of certain aspects, features, and embodiments of the present invention.

[0038] It should be understood that the terms described in the present invention are only for describing special embodiments and are not intended to limit the present invention. In addition, for the numerical range in the present invention, it should be understood that each intermediate value between the upper and lower limits of the scope is also specifically disclosed. Each smaller range between the intermediate value in any stated value or stated range and any other stated value or intermediate value in the described range is also included in the present invention. The upper and lower limits of these smaller ranges can be independently included or excluded in the scope.

[0039] Unless otherwise indicated, all technical and scientific terms used herein have the same meanings as those generally understood by those skilled in the art. Although the present invention describes only preferred methods and materials, any methods and materials similar or equivalent to those described herein may also be used in the implementation or testing of the present invention. All documents mentioned in this specification are incorporated by reference to disclose and describe the methods and / or materials associated with the documents. In the event of a conflict with any incorporated document, the content of this specification shall prevail.

[0040] It will be apparent to those skilled in the art that various modifications and variations may be made to the specific embodiments of the present invention description without departing from the scope or spirit of the present invention. Other embodiments derived from the present invention description will be apparent to the skilled artisan. The present invention description and examples are exemplary only.

[0041] The words “include,” “including,” “have,” “contain,” etc. used in this document are open-ended terms, meaning including but not limited to.

[0042] In a first aspect, the present invention provides a method for preparing cellulose nanocrystals, comprising the following steps:

[0043] Carboxylation is performed on cellulose and then sulfonation is performed to obtain cellulose modified with carboxylation and sulfonation groups;

[0044] Cellulose modified with carboxyl and sulfonate groups is stripped to obtain cellulose nanocrystals.

[0045] In a preferred embodiment of the present invention, the cellulose comprises one or more of refined cotton, dry bleached bagasse or dry bleached wood pulp.

[0046] Refined cotton is a commercially available refined cotton product that has been processed from natural cotton; dry bleached wood pulp includes bleached eucalyptus pulp, which is mainly composed of cellulose and has a high degree of crystallinity. It is a fibrous material with a diameter of 10 to 20 microns and a length of the millimeter level.

[0047] In a preferred embodiment of the present invention, the method for carboxylating cellulose comprises the following steps: alkalizing the cellulose and then adding an organic acid to perform a carboxylation reaction to obtain carboxylated cellulose.

[0048] In a preferred embodiment of the present invention, the alkaline agent used in the alkalization treatment includes potassium hydroxide or sodium hydroxide; the temperature of the alkalization treatment is 30-35° C., and the time is 40 minutes.

[0049] In a preferred embodiment of the present invention, the alkaline agent needs to be prepared into a mixed solution for alkalization treatment; the solvent in the mixed solution includes water and an organic solvent in a volume ratio of 1: (10-15); the mass ratio of the alkaline agent to water in the mixed solution is 1:10; the organic solvent includes isopropanol and / or anhydrous ethanol.

[0050] In a preferred embodiment of the present invention, when the organic solvent is isopropanol and anhydrous ethanol, the volume ratio of isopropanol to anhydrous ethanol is (1-3):1.

[0051] In a preferred embodiment of the present invention, the mass ratio of cellulose to the alkaline reagent is (1-3):1; the molar ratio of the glucose unit in the cellulose to the organic acid is (1-5):1; the temperature of the carboxylation reaction is 70°C and the time is 2-4h.

[0052] If the mass ratio of the cellulose raw material to the alkaline reagent is higher or lower than the parameters recorded above, the final yield of nanocellulose will be greatly reduced.

[0053] In a preferred embodiment of the present invention, the molar ratio of the number of glucose units in the cellulose to the organic acid is (1.5-4):1; the temperature of the carboxylation reaction is 70° C., and the time is 3 hours.

[0054] In a preferred embodiment of the present invention, the organic acid comprises one or more of chloroacetic acid, methyl chloroacetate, ethyl chloroacetate and isopropyl chloroacetate.

[0055] In a preferred embodiment of the present invention, the sulfonation treatment method comprises the following steps: mixing carboxylated cellulose and sulfuric acid solution to react to obtain carboxylated and sulfonated double-group modified cellulose.

[0056] In a preferred embodiment of the present invention, the concentration of the sulfuric acid solution is 45-65wt.%; the usage ratio of carboxylated cellulose and sulfuric acid solution is 1g:(10-40)mL; the reaction temperature is 25-65°C, and the reaction time is 2-48h.

[0057] The reaction temperature is low and the reaction time is prolonged.

[0058] In a preferred embodiment of the present invention, the stripping method comprises the following steps: adding carboxylation and sulfonation double-group modified cellulose into water so that the concentration of carboxylation and sulfonation double-group modified cellulose is 2 to 4 wt.%, then adjusting the pH to 6 to 8, stirring and soaking (the stirring speed of the stirring and soaking is 100 to 2000 rpm, and the time is 30 min to 12 h) and then stripping to obtain cellulose nanocrystals.

[0059] In a preferred embodiment of the present invention, the peeling method includes high-speed shearing (high-speed stirring shear rate of 10000rpm, continuous shearing for 20min), high-pressure homogenization (homogenization parameters: 40-45Mpa, continuous homogenization 5-10 times), ultrasound (ultrasound power 800w, ultrasound time 5-15min), ball milling or grinding (grinding power 4kw, grinding speed 2000-2900rpm, grinding time 20-30min) treatment, and the number of treatments is 5 to 10 times.

[0060] In a second aspect, the present invention provides cellulose nanocrystals prepared by the above preparation method.

[0061] The third aspect of the present invention provides an application of the above-mentioned cellulose nanocrystals in the preparation of battery negative electrode materials.

[0062] Unless otherwise specified, the raw materials used in the following examples and comparative examples of the present invention can be obtained through commercial sources.

[0063] The chemical reagents used in the following examples and comparative examples of the present invention are all analytically pure.

[0064] The model of the refined cotton used in the following embodiments and comparative examples of the present invention is M650.

[0065] Example 1

[0066] A method for preparing cellulose nanocrystals:

[0067] (1) 9 g of purified cotton is further ground into cotton powder with a diameter of about 10 to 20 μm and a length of about 500 to 1000 mm using a grinder.

[0068] (2) Add 3 g of potassium hydroxide and 30 g of deionized water into a three-necked flask. After the potassium hydroxide is completely dissolved, add 300 mL of isopropanol and stir evenly to obtain a mixed solution of potassium hydroxide, water and isopropanol.

[0069] (3) Add the cotton powder (containing 0.055 mol of glucose unit) obtained in step (1) to the mixed solution obtained in step (2), stir evenly and alkalize at 30°C for 40 min, then add 1.8 g of chloroacetic acid (0.019 mol), 2.5 g of isopropyl chloroacetate (0.018 mol), 0.03 g of potassium iodide and 0.015 g of sodium acetate, stir evenly and react at 70°C for 3 h, then filter the reaction solution to obtain a crude product, then backwash the crude product with deionized water, and finally filter to obtain a carboxylated cellulose pulp filter cake.

[0070] (4) After drying the carboxylated cellulose slurry filter cake obtained in step (3), a carboxylated cellulose nanofiber solid material is obtained, and the yield of the carboxylated cellulose nanofiber solid material is 86%.

[0071] (5) subjecting the carboxylated cellulose nanofiber solid obtained in step (4) to a sulfonation reaction treatment, i.e., adding 5 g of the carboxylated cellulose nanofiber solid to 200 mL of a 45 wt.% sulfuric acid solution at 25°C for reaction for 48 h. After the reaction is completed, the reaction solution is filtered to obtain a crude product, and the crude product is backwashed with water and filtered to obtain a cellulose pulp filter cake modified with a carboxylation and sulfonation double group.

[0072] (6) Add water to the carboxylation and sulfonation double-group modified cellulose pulp filter cake obtained in step (5) to prepare a cellulose dispersion with a concentration of 2 wt.%, and adjust the pH value to 6 with sodium hydroxide solution. After soaking and stirring at 100 rpm for 12 hours, the dispersion is homogenized 8 times with a 60 MPa homogenizer. The resulting dispersion is then repeatedly centrifuged, washed with water 3 times, and redispersed to obtain a carboxylation and sulfonation double-group cellulose nanocrystal aqueous dispersion (cellulose nanocrystal aqueous dispersion).

[0073] The appearance of the carboxylated and sulfonated bi-group cellulose nanocrystals prepared in this example is shown in FIG. Figure 1 , SEM images are shown in Figure 2 .

[0074] X-ray diffraction analysis shows that the carboxylated and sulfonated dimethylcellulose nanocrystals prepared in this embodiment still maintain the crystalline structure of cellulose I. According to the calculation method of Segal et al., its crystallinity CI is 75.9%, indicating that the purity of the obtained carboxylated and sulfonated dimethylcellulose nanocrystals is relatively high (the crystallinity of the refined cotton used in this embodiment is 78.8% measured by the same method); and the transmission electron microscopy test results show that the diameter of the carboxylated and sulfonated dimethylcellulose nanocrystals prepared in this embodiment is about 10nm to 40nm, and the length is about 100~500nm (see Figure 3 ).

[0075] Example 2

[0076] A method for preparing cellulose nanocrystals:

[0077] (1) 7 g of refined cotton was further ground into cotton powder with a diameter of about 10 to 20 μm and a length of about 500 to 1000 mm using a grinder.

[0078] (2) Add 3.5 g of potassium hydroxide and 35 g of deionized water into a three-necked flask. After the potassium hydroxide is completely dissolved, add 350 mL of isopropanol and stir evenly to obtain a mixed solution of potassium hydroxide, water and isopropanol.

[0079] (3) Add the cotton powder (containing 0.044 mol of glucose unit) obtained in step (1) to the mixed solution obtained in step (2), stir evenly, alkalize at 30°C for 40 min, and then add 2.1 g of chloroacetic acid (0.022 mol) and 3.0 g of isopropyl chloroacetate (0.022 mol). 、 0.036g potassium iodide and 0.018g sodium acetate were stirred evenly and reacted at 70°C for 3h. The reaction solution was then filtered to obtain a crude product. The crude product was then backwashed with deionized water and finally filtered to obtain a carboxylated cellulose pulp cake.

[0080] (4) Drying the carboxylated cellulose slurry cake obtained in step (3) to obtain a carboxylated cellulose nanofiber solid.

[0081] (5) subjecting the carboxylated cellulose nanofiber solid obtained in step (4) to a sulfonation reaction treatment, i.e., adding 5 g of the carboxylated cellulose nanofiber solid to 50 mL of a 45 wt.% sulfuric acid solution at 65° C. for reaction for 2 h. After the reaction is completed, the reaction solution is filtered to obtain a crude product, and the crude product is backwashed with water and filtered to obtain a cellulose pulp filter cake modified with carboxylation and sulfonation double groups.

[0082] (6) Add water to the carboxylation and sulfonation double-group modified cellulose pulp filter cake obtained in step (5) to prepare a cellulose dispersion with a concentration of 4 wt.%, and adjust the pH value to 8 with lithium hydroxide solution. After soaking and stirring at 2000 rpm for 30 minutes, homogenize it 8 times with a 60 MPa homogenizer, and then repeatedly centrifuge and wash it with water 3 times, and then re-disperse it to obtain a carboxylation and sulfonation double-group cellulose nanocrystal aqueous dispersion (cellulose nanocrystal aqueous dispersion).

[0083] X-ray diffraction analysis shows that the carboxylated and sulfonated dimethylcellulose nanocrystals prepared in this embodiment still retain the crystalline structure of cellulose I. According to the calculation method of Segal et al., its crystallinity CI is 74.6%, indicating that the purity of the obtained carboxylated and sulfonated dimethylcellulose nanocrystals is very high (the crystallinity of the refined cotton used in this embodiment is 78.8% measured by the same method); and the transmission electron microscopy test results show that the diameter of the carboxylated and sulfonated dimethylcellulose nanocrystals prepared in this embodiment is about ten to several tens of nanometers, and the length is about 100 to 500nm (see Figure 4 ).

[0084] Table 1 Performance parameters of carboxylation and sulfonation dimeric cellulose nanocrystals prepared in Example

[0085]

[0086] Example 3

[0087] A method for preparing a negative electrode material for a battery:

[0088] In the negative electrode slurry, the solid content is 40%, and the mass ratio of negative electrode active material 1 (carbon black), negative electrode active material 2 (Si / C composite, the mass ratio of Si and C is 1:1), conductive material 1 (SP), conductive material 2 (carbon nanotubes), CNC-Na (prepared in Example 1), PAA (polyacrylic acid) and SBR (styrene-butadiene rubber) is 79.95%: 15.05%: 1.4%: 0.1%: 1%: 2%: 0.5%, and the sum of the mass is 100%; the amount of CNT used is 0.1% of the total mass of negative electrode active material 1, negative electrode active material 2, conductive material 1, conductive material 2, CNC-Na, PAA and SBR.

[0089] (1) Add the negative electrode active material and conductive agent powder into a stirring device according to a certain proportion and stir evenly (stirring parameters are: revolution 1000 rpm, rotation 600 rpm, dispersion time 300 s).

[0090] (2) Add an appropriate amount of deionized water, add carboxylated and sulfonated bi-group cellulose nanocrystals (CNC-Na), PAA, and CNT into a stirring device in proportion, and stir evenly (stirring parameters are: revolution 1000 rpm, rotation 600 rpm, and dispersion time 300 s).

[0091] (3) The slurry obtained in step (2) was dispersed (dispersion conditions: stirring speed 2000 rpm, stirring time 1800 s).

[0092] (4) The slurry obtained in step (3) is stirred again and stirred evenly (stirring parameters are: revolution 2000 rpm, rotation 1200 rpm, dispersion time 180 s).

[0093] (5) Filter the slurry obtained in step (4) (filter bag parameters: 100 μm).

[0094] (6) SBR and deionized water were added to the slurry obtained in step (5) in proportion, and then dispersed and vacuumed (parameters: revolution 1000 rpm, rotation 600 rpm, dispersion time 300 s).

[0095] (7) Test the viscosity of the slurry obtained in step (6).

[0096] (8) The slurry prepared in step (7) is coated on the current collector to obtain a negative electrode material for a battery. The coating process is as follows: width 10.3 cm, coating length: 60 cm, coating speed: 18 m / min; drying temperature: 55° C., dry film thickness: 100 μm.

[0097] In all steps of the above stirring process, the slurry temperature was controlled at 25±2°C.

[0098] Comparative Example 1

[0099] Same as Example 3, except that CNC-Na (prepared in Example 1) is replaced with an equal mass of CMC-Na (sodium carboxymethyl cellulose).

[0100] Effect Example 1

[0101] The relevant properties of the slurry obtained in Example 3 and Comparative Example 1 were tested, and the testing method was as follows:

[0102] The test temperature is 25℃, relative humidity is 55%~65%,

[0103] (I) Fineness test method (scraper fineness meter: QXD type):

[0104] According to the national standard "GB / T 6753.1-2007 Determination of grinding fineness of paints, varnishes and printing inks", the measurement steps are as follows:

[0105] (1) Place the thoroughly cleaned and dried scraper on a flat, level, non-slip surface;

[0106] (2) Drop enough sample into the deepest part of the groove, i.e. the part with the largest scale value, and allow the sample to slightly overflow;

[0107] (3) Hold the scraper with the thumb and index finger of both hands, and place the scraper blade horizontally at the maximum scale value of the scraper (at the edge of the sample) so that the long side of the scraper is parallel to the wide side of the scraper and in vertical contact with the scraper surface. Scrape the scraper from the maximum scale value to the minimum scale value within 1 to 2 seconds;

[0108] (4) Immediately after scraping the sample (within 5 seconds), make your line of sight at an angle of 20 to 30 degrees to the groove plane, observe the evenly exposed areas of the particles in the groove against the light, and record the corresponding scale value.

[0109] (II) Viscosity test method (viscometer model: NDJ-8S):

[0110] The specific operation steps of viscosity test are as follows:

[0111] Choose the appropriate rotor and speed: Choose the appropriate rotor and speed according to the viscosity of the sample.

[0112] Constant temperature treatment: Keep the sample and rotor at a specified temperature (usually 25±0.5℃) and keep them stable.

[0113] Measurement: Immerse the rotor vertically into the center of the sample and start rotating. Wait for the pointer to stabilize before reading the value and take the average value after multiple measurements.

[0114] (III) Test methods for cohesive peeling force and current collector peeling force (electric peeling force tester model: ZQ-990LA-2): GB / T 5284-2009 “Test methods for tensile peeling properties of composite materials”;

[0115] The test steps are as follows:

[0116] 1. Material preparation: The test requires a certain number of lithium-ion batteries and battery testing equipment. The testing equipment mainly includes positioning devices, fixtures, force meters, etc.

[0117] 2. Test steps

[0118] (1) Place the battery on the positioning device, making sure the electrodes are flush with the fixture surface and not skewed.

[0119] (2) Connect the peel force sensor to the force gauge and install it on the fixture.

[0120] (3) Calibrate the peel force sensor and force meter.

[0121] (4) Clamp the electrode with a clamp and apply a peeling force.

[0122] (5) Record the force value when the electrode is peeled off and calculate the average value.

[0123] (6) Perform multiple tests and calculate the mean and standard deviation.

[0124] (IV) Conductivity test method: The conductivity test of the slurry uses a conductivity meter. After calibration with a conductivity standard solution, the electrode is cleaned with deionized water and blown dry, and then the conductivity of the slurry is tested at room temperature.

[0125] Table 2 Relevant test data of the slurry obtained in Example 3 and Comparative Example 1

[0126]

[0127] The embodiments described above are only descriptions of the preferred modes of the present invention, and are not intended to limit the scope of the present invention. Without departing from the design spirit of the present invention, various modifications and improvements made to the technical solutions of the present invention by ordinary technicians in this field should all fall within the protection scope determined by the claims of the present invention.

Claims

1. A method for preparing cellulose nanocrystals, characterized in that: The following steps are involved: Carboxylation is performed on cellulose and then sulfonation is performed to obtain cellulose modified with carboxylation and sulfonation groups; The carboxylation and sulfonation double-group modified cellulose is subjected to a stripping treatment to obtain the cellulose nanocrystal.

2. The preparation method according to claim 1, characterized in that: The method for carboxylating cellulose comprises the following steps: alkalizing the cellulose and then adding an organic acid to carry out a carboxylation reaction to obtain carboxylated cellulose.

3. The preparation method according to claim 2, characterized in that: The alkaline reagent used in the alkalization treatment includes potassium hydroxide or sodium hydroxide; The temperature of the alkalization treatment is 30-35° C. and the time is 40 minutes.

4. The preparation method according to claim 3, characterized in that: The mass ratio of the cellulose to the alkaline reagent is (1-3):1; The molar ratio of the number of glucose units in the cellulose to the organic acid is (1-5):1; The temperature of the carboxylation reaction is 70° C. and the time is 2 to 4 hours.

5. The preparation method according to claim 2, characterized in that: The sulfonation treatment method comprises the following steps: mixing the carboxylated cellulose and a sulfuric acid solution for reaction to obtain the carboxylated and sulfonated double-group modified cellulose.

6. The preparation method according to claim 5, characterized in that: The concentration of the sulfuric acid solution is 45-65 wt.%; the dosage ratio of the carboxylated cellulose to the sulfuric acid solution is 1 g: (10-40) mL; The reaction temperature is 25-65°C and the reaction time is 2-48 hours.

7. The preparation method according to claim 1, characterized in that: The stripping treatment method comprises the following steps: adding the carboxylation and sulfonation double-group modified cellulose into water, adjusting the pH to 6-8, stirring and soaking, and then stripping to obtain the cellulose nanocrystals.

8. A cellulose nanocrystal prepared by the preparation method according to any one of claims 1 to 7.

9. Use of the cellulose nanocrystals according to claim 8 in the preparation of battery negative electrode materials or separators.